Optimized detection of germ cell neoplasia in situ in contralateral biopsy reduces the risk of second testis cancer. (13th June 2022) - Rajpert‐De Meyts, Ewa; Jørgensen, Niels; Petersen, Jørgen Holm; Almstrup, Kristian; Aksglaede, Lise; Lauritsen, Jakob; Rørth, Mikael; Daugaard, Gedske; Skakkebæk, Niels E.
Abstract: Objective: To evaluate whether optimized and standardized diagnostic procedures would improve detection of germ cell neoplasia in situ (GCNIS) in the contralateral testis of patients with testicular germ cell tumour (TGCT) and decrease the rate of metachronous tumours, which in a nationwide Danish study was estimated to be 1.9%. Patients and Methods: This was a retrospective analysis of outcomes in 655 patients with TGCT who underwent contralateral biopsies (1996–2007) compared with those in 459 non‐biopsied TGCT controls (1984–1988). The biopsies were performed using a standardized procedure with immunohistochemical GCNIS markers and assessed by experienced evaluators. Initial histopathology reports were reviewed, and pathology and survival data were retrieved from national Danish registers. In 604/608 patients diagnosed as GCNIS‐negative (four were lost to follow‐up), the cumulative incidence of metachronous TGCT was estimated in a competing risk setting using the Grey method. All cases of metachronous TGCT were re‐examined using immunohistochemistry. Results: Germ cell neoplasia in situ was found in 47/655 biopsied patients (7.2%, 95% confidence interval [CI] 5.4–9.5%). During the follow‐up period (median 17.3 years) five of the 604 GCNIS‐negative patients developed a TGCT. In 1/5 false‐negative biopsies, GCNIS was found on histological revision using immunohistochemistry and 2/5 biopsies were inadequate because of too small size. The estimated cumulative incidence rate of second tumour after 20 years of follow‐up was 0.95% (95% CI 0.10%–1.8%) compared with 2.9% (95% CI 1.3%–4.4%) among the non‐biopsied TGCT patients ( P  = 0.012). The estimates should be viewed with caution due to the small number of patients with metachronous TGCT. Conclusions: Optimized diagnostic procedures improved the detection rate of GCNIS in patients with TGCT and minimized their risk of developing metachronous bilateral cancer. Urologists should be aware of the importance of careful tissue excision (to avoid mechanical compression) and the need of adequate biopsy size. Performing contralateral biopsies is beneficial for patients' care and should be offered as a part of their management.